Innovations in Higher Education (IntechOpen, 2021)
Higher education contributes to the development of countries and their competitiveness in a global marketplace. However, to remain relevant and meet the demands of an ever-changing world, institutions and their operations must progress in unison with the changing world in which they function. Innovation can play a critical role in transforming and advancing practice and therein address socio-economic, organizational, operational and social challenges. The complexity and scope of higher education opens up the possibilities and potential for innovations to transpire in diverse settings and contexts. This book is a collection of easy-to-follow, vignette-based innovations that have transformed or advanced practice and in doing so contributed to ensuring the relevance and value of higher education in a continuously changing world.